(3GdJegjO aj JfRjd GdaQhY Ydi GdCUhds - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s ((3YeQ Hf YHO GdQMef Hf YHO Gddg Hf MSjf Hf YHO Gddg GdHjQhfi s)
(3ChdgG (B:s
(3GdMeO ddg eRjd CYPGQ Gdecdajf HZQTGO GdYbhd hHYO aEf CUhd Gdabg Yde YXje faYg hbOQg hbO egOJ HcJGHi gPG WQjb GdJNQjL dcd Pi ePgH haJMJ Hg HGH GdJaQjY dcd Pi eWdH s
(3BNQgG (B:s
(3ceG dh Mce dfaSg Ke JZjQ ELJgGOg JZjQkG dGjbJVi GdfbV Ke JQGaY Edjg ZQeGA GdhGbYI GdJi Mce ajgG aEfg jeVi Mceg GdChd hEf COi ELJgGOi Edi Cf ZjQg CUhH ceG PcQg GdQGaYi ai cJGH GdbVGA , hGddg CYde s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ eOGNd GdCHhGH hGdeSGFd HeOGO CMeQ s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3CUhd Gdabgs